2015
DOI: 10.1097/dcr.0000000000000425
|View full text |Cite
|
Sign up to set email alerts
|

Spin Is Common in Studies Assessing Robotic Colorectal Surgery

Abstract: Spin occurred in >80% of included studies. Many studies concluded that robotic surgery was as safe as more traditional techniques, despite small sample sizes and limited follow-up. Authors often failed to recognize the difference between nonsignificance and equivalence. Failure to disclose financial relationships, which could represent potential conflict(s) of interest, is concerning. Readers of these articles need to be critical of author conclusions, and publishers should ensure that conclusions correspond w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(9 citation statements)
references
References 9 publications
1
8
0
Order By: Relevance
“…Our sample size (n = 87) was comparable to other spin studies with sample sizes of 100 to 150 articles (5). However, the amount For profit 6 (6.9) of spin we found is higher than described in previous studies (3,5,7,8,(10)(11)(12)(18)(19)(20)(21)(22). Spin has its implications for research and therefore can hinder us in finding a treatment for tinnitus.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Our sample size (n = 87) was comparable to other spin studies with sample sizes of 100 to 150 articles (5). However, the amount For profit 6 (6.9) of spin we found is higher than described in previous studies (3,5,7,8,(10)(11)(12)(18)(19)(20)(21)(22). Spin has its implications for research and therefore can hinder us in finding a treatment for tinnitus.…”
Section: Discussionsupporting
confidence: 68%
“…The common advise to authors is to adhere to reporting guidelines in general (e.g., CONSORT guidelines for RCTs) and omit any form of spin in their articles (27). Readers should be critical when reading articles and recognize forms of spin, especially in the abstract and conclusion of publications (10,19,20).…”
Section: Discussionmentioning
confidence: 99%
“…5 Operative time, conversion rates, length of stay, nodal yield, margin status, complications, survival, recurrence rates, and urological and sexual functions are some of the outcomes studied. 4 7 Documented outcomes reflect precision surgery which in turn relates to an improved ability to accurately identify, separate, and excise.…”
Section: Tablementioning
confidence: 99%
“…Furthermore, the dividing line between significance and non-significance can be increasingly manipulated. An eyebrow-raising analysis of 38 studies comparing robotic colorectal surgery to other approaches found that “spin”—defined as “specific reporting that could distort the interpretation of results and mislead readers”—affected over 80% of the included studies ( 54 ).…”
Section: Pushing the Boundaries Of Current Technology: Robotics And Mmentioning
confidence: 99%